Bovine autosomal recessive alpha-mannosidosis in an Aberdeen Angus herd from Argentina - Morris, Winston Eduardo (2023)
An outbreak of α-mannosidosis in a bovine herd from Buenos Aires province is reported. Postmortem examination, histology, lectin histochemistry and electron microscopy were performed on five calves born with nervous signs. Hair samples from dams and calves were genetically analysed. The α-mannosidase gene including exon 7 was amplified and sequenced. At postmortem examination, no gross changes were evident. Histologically, cytoplasmic neuronal vacuolation in the brain and cerebellum of the five calves, staining moderately to intensively, with lectin histochemistry was evident. Ultrastructurally, vacuoles containing finely granulated material in the cytoplasm of neurons, myelin degeneration and axonal swelling were seen in the brain. Genetic analysis revealed a heterozygous carrier state for 961T→C transition in the exon 7 of α-mannosidosis gene of four cows, and a recessive homozygous state for 961T→C transition in the same genes in the calves analysed. This highlights the importance of identifying and removing animals carrying the α-mannosidosis mutated gene.